2021
DOI: 10.1021/acs.jpclett.1c01774
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Mechanism for Tuning the Fluorescence of Fluorescein Derivatives: The Role of the Conical Intersection and nπ* State

Abstract: Although a large number of fluorescein derivatives have been developed and applied in many different fields, the general mechanisms for tuning the fluorescence of fluorescein derivatives still remain uncovered. Herein, we found that the fluorescence quenching of neutral form of fluorescein derivatives in acidic medium resulted from a dark nπ* state, whereas the fluorescence of the anionic form of fluorescein derivatives in the gas phase and alkaline solutions was tuned by minimal energy conical intersection (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 43 publications
2
46
0
Order By: Relevance
“…Moreover, the dihedral angle between FL and Q group has been changed obviously. As previous studies [60,61], the large geometry change between S 0 and S 1 states may lead to a fast internal conversion and thereby quenching the fluorescence. Thus, the fluorescent quenching mechanism of FQ-DNP is TICT.…”
Section: Fmos Electron-hole Analysis and Detection Mechanismsupporting
confidence: 51%
“…Moreover, the dihedral angle between FL and Q group has been changed obviously. As previous studies [60,61], the large geometry change between S 0 and S 1 states may lead to a fast internal conversion and thereby quenching the fluorescence. Thus, the fluorescent quenching mechanism of FQ-DNP is TICT.…”
Section: Fmos Electron-hole Analysis and Detection Mechanismsupporting
confidence: 51%
“…39 In particular, the excited-state behaviors and related photochemical as well as photophysical properties of target molecules could be changed by the solvent polarity. [40][41][42][43][44][45][46] Thus, in this work, we mainly focused on exploring the excited-state dynamical process and relative ESIPT mechanism for BI3HC in organic solvents with different polarities. Briefly, our simulated results present a novel dynamical mechanism for the BI3HC fluorophore that differs from previous attributions and conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it can be found that the energy barriers of reverse ground-state intramolecular proton transfer (RGSIPT) of HQ, HQS, and HQSe are far lower than the energy barriers of ground-state intramolecular proton transfer (GSIPT) and ESIPT. Thus, it can be found that the three compounds can quickly return to the enol form in the S 0 state, and it is favorable to enhance the effective acting time of sunscreen.…”
Section: Results and Discussionmentioning
confidence: 99%